Antimicrobial susceptibility profile and research of mec A and erm genes in coagulase-negative staphylococci isolated from platelet concentrates bags (Brazilian Journal of Pharmaceutical Sciences, 2017)
In recent years, several studies have described the clinical impact of bacterial infection associated with transfusion of platelet concentrates (PCs). Among the blood components, PCs are responsible for the highest rates of bacterial contamination as well as septic transfusion reactions. We assessed antimicrobial susceptibility profile, resistance to methicillin (MRCoNS), and resistance to macrolides, lincosamides and streptogramins of group B (MLSB) of 16 coagulase-negative staphylococci (CoNS) isolates from an investigation in 691 PCs bags. We then compared conventional and automated phenotypic methods, disc diffusion test (DD) and VITEK(r) 2, respectively as well as phenotypic and genotypic methods (Polymerase Chain Reaction - PCR). All CoNS were susceptible to vancomycin. The disc diffusion test characterized 18.75% as MRCoNS and 37.5% with inducible resistance to MLSB (iMLSB), and with VITEK(r) 2, 6.3% and 31.25%, respectively. The mecA gene was detected in 18.75% and the erm gene in 31.25% of the isolates. In this study, we found equal percentage values between presence of the mecA gene by PCR and resistance to methicillin using cefoxitin by DD test, evidence of the erm gene by PCR, and iMLSB resistance by automation (VITEK(r) 2). Moreover, we identified three strains with beta-lactamase overproduction, and the occurrence of a bigger mistake was verified when automation was compared with DD test. And we observed that D-test was the most reliable for the detection of iMLSB resistance in Staphylococcus sp.